2020
DOI: 10.1038/s41467-020-18594-3
|View full text |Cite
|
Sign up to set email alerts
|

IRES-targeting small molecule inhibits enterovirus 71 replication via allosteric stabilization of a ternary complex

Abstract: Enterovirus 71 (EV71) poses serious threats to human health, particularly in Southeast Asia, and no drugs or vaccines are available. Previous work identified the stem loop II structure of the EV71 internal ribosomal entry site as vital to viral translation and a potential target. After screening an RNA-biased library using a peptide-displacement assay, we identify DMA-135 as a dose-dependent inhibitor of viral translation and replication with no significant toxicity in cell-based studies. Structural, biophysic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(113 citation statements)
references
References 39 publications
5
108
0
Order By: Relevance
“…Finally, high-throughput screening approaches have led to identification of novel highly tunable scaffolds, as is the case with the amiloride scaffold initially identified by the Al-Hashimi laboratory ( 87 ). Our laboratory has since synthesized ∼60 derivatives, some of which have high specificity for select viral RNAs ( 88 , 89 , 90 ). Other scaffolds investigated for RNA binding through scaffold optimization have included benzimidazoles ( 91 ), aminoglycoside–benzimidazole conjugates ( 92 , 93 , 94 , 95 ), 2-aminobenzoxazoles ( 96 ), thienopyridines ( 97 ), diarylpyridines ( 98 ), diaryltriazines ( 99 ), oxazolidinones ( 100 ), 3,5-diamino-piperidines ( 101 , 102 ), diphenylfurans ( 14 , 67 , 103 , 104 , 105 ), verapamil ( 106 ), methylquinolinium derivatives ( 107 ), aminoquinolones ( 108 ), and triptycene-based molecules designed for DNA and RNA junctions ( 109 ) ( Fig.…”
Section: Framework 2: Potential Existence Of An Rna-biased Chemical Smentioning
confidence: 99%
“…Finally, high-throughput screening approaches have led to identification of novel highly tunable scaffolds, as is the case with the amiloride scaffold initially identified by the Al-Hashimi laboratory ( 87 ). Our laboratory has since synthesized ∼60 derivatives, some of which have high specificity for select viral RNAs ( 88 , 89 , 90 ). Other scaffolds investigated for RNA binding through scaffold optimization have included benzimidazoles ( 91 ), aminoglycoside–benzimidazole conjugates ( 92 , 93 , 94 , 95 ), 2-aminobenzoxazoles ( 96 ), thienopyridines ( 97 ), diarylpyridines ( 98 ), diaryltriazines ( 99 ), oxazolidinones ( 100 ), 3,5-diamino-piperidines ( 101 , 102 ), diphenylfurans ( 14 , 67 , 103 , 104 , 105 ), verapamil ( 106 ), methylquinolinium derivatives ( 107 ), aminoquinolones ( 108 ), and triptycene-based molecules designed for DNA and RNA junctions ( 109 ) ( Fig.…”
Section: Framework 2: Potential Existence Of An Rna-biased Chemical Smentioning
confidence: 99%
“…Jesse Calderon et al found DMA-135, an inhibitor targeting Enterovirus 71 stem loop 2 (SL2), induces a conformational change and stabilizes the ternary complex with AUF1 (AU-rich element RNA-binding protein 1) incorporated, thus repressing translation. By calculating the NMR structures of SL2 complexed with DMA-315 using NOEs and RDCs, they revealed that DMA-315 changes the interhelical angle between the upper and lower helices of SL2 by 77 degrees [ 143 ]. In our group, we characterized the interactions between the Hsp90 middle domain (Hsp90M) and two active compounds SOMCL-16-171 and SOMCL-16-175 by conducting chemical shift perturbation and mutagenesis analysis.…”
Section: Nmr In Fragment-based Drug Discoverymentioning
confidence: 99%
“…As a software, MOE (Molecular Operating Environment) [15] was used, which is a powerful tool to find suitable ligand‐protein conformations. The software has already proven highly successful for a range of applications [16–21] . With the combination of wet experiments including a variety of mutants and substrates we were able to understand this unique and unprecedented behavior regarding the enantioselectivity of these enzymes.…”
Section: Introductionmentioning
confidence: 99%